Mediterranean Outflow Water dynamics during the past ~570 kyr: Regional and global implications. (22nd June 2017) - Kaboth, Stefanie; de Boer, Bas; Bahr, André; Zeeden, Christian; Lourens, Lucas J.
Abstract: The Gulf of Cadiz constitutes a prime area to study teleconnections between the North Atlantic Ocean and climate change in the Mediterranean realm. In particular, the highly saline Mediterranean Outflow Water (MOW) is an important modulator of the North Atlantic salt budget on intermediate water levels. However, our understanding of its paleoceanographic evolution is poorly constrained due to the lack of high‐resolution proxy records that predate the last glacial cycle. Here we present the first continuous and high‐resolution (~ 1 kyr) benthic δ 18 O and δ 13 C as well as grain size records from Integrated Ocean Drilling Program Site U1386 representing the last ~570 kyr. We find three distinct phases of MOW variability throughout the Late to Middle Pleistocene at Site U1386 associated with prominent shifts in its composition and flow strength. We attribute this long‐term variability to changes in water mass sourcing of the MOW. Superimposed on the long‐term change in water mass sourcing is the occurrence of distinct and precession paced δ 18 O enrichment events, which contrast the pattern of global ice volume change as inferred from the global mean δ 18 O signal (i.e., LR04) but mimics that of the adjacent Mediterranean Sea. We attribute these enrichment events to a profound temperature reduction and salinity increases of the MOW, aligning with similar changes in the Mediterranean source region. These events might further signify ice volume increases as inferred from significant sea level drops recorded in the Red Sea and/or increased influence of North Atlantic intermediate water masses when MOW influence was absent at Site U1386. Key Points: Middle to Late Pleistocene Mediterranean Outflow variability Precession paced glacial δ 18 O enrichment events Shift in the sourcing of Mediterranean Outflow Water from Eastern to Western Mediterranean Sea at ~130 ka